Efficacy of axillary versus infraclavicular brachial plexus block in preventing tourniquet pain: A randomised trial. Issue 1 (January 2019) - Brenner, David; Iohom, Gabriella; Mahon, Padraig; Shorten, George
Abstract : BACKGROUND: Axillary and infraclavicular brachial plexus blocks are commonly used for upper limb surgery. Clinicians require information on the relative benefits of each to make a rational selection for specific patients and procedures. OBJECTIVES: The main objective of the study was to compare axillary and infraclavicular brachial plexus block in terms of the incidence and severity of tourniquet pain. DESIGN: Single blinded, randomised trial. SETTING: University affiliated hospital, level-1 trauma centre. PATIENTS: Age more than 18 years, ASAI-III patients undergoing orthopaedic surgery distal to the elbow, with an anticipated tourniquet duration of more than 45 min were recruited. INTERVENTIONS: Patients underwent either ultrasound guided axillary brachial plexus block or infraclavicular block (ICB). MAIN OUTCOME MEASURES: Incidence of tourniquet pain (onset, severity, associated haemodynamic changes) and block characteristics (block performance/onset times, distribution, incidence of adverse events, patient satisfaction) were recorded. RESULTS: Eighty two patients (40 in the axillary block and 42 in the ICB group) were recruited. The incidence (5/36 and 3/35; P = 0.71), onset time (73.0 ± 14.8 and 86.6 ± 5.7 min; P = 0.18) and severity (mild/moderate; 4/1 and 1/2; P = 0.51) of tourniquet pain were similar in the two groups. The incidence of paraesthesia during block performance, and block performance time were greater in the axillary block group ( P = 0.0054 and 0.012, respectively). The volume of local anaesthetic administered was greater in the ICB group ( P < 0.01). ICB was associated with a greater degree of sensory block in the distributions of both the axillary nerve and the medial cutaneous brachial nerve ( P < 0.01). Overall patient satisfaction and incidence of inadvertent vascular puncture were similar in the two groups. CONCLUSION: For surgical procedures which are of moderate duration, infraclavicular and axillary blocks are associated with similar incidences of tourniquet pain. Other factors appear to differentiate between these two blocks, namely block performance time, incidence of paraesthesia and dose of local anaesthetic. TRIAL REGISTRATION: ClinicalTrials.gov ID: NCT02714738.